Mutational analysis of the Drosophila DNA repair and recombination gene mei-9. - Yildiz, O.; Kearney, H.; Kramer, B.C.; Sekelsky, J.J. (Genetics, 2004)
Drosophila mei-9 is essential for several DNA repair and recombination pathways, including nucleotide excision repair (NER), interstrand crosslink repair, and meiotic recombination. To better understand the role of MEI-9 in these processes, we characterized 10 unique mutant alleles of mei-9. These include a P-element insertion that disrupts repair functions but not the meiotic function; three nonsense mutations, one of which has nearly wild-type levels of protein; three missense mutations, one of which disrupts the meiotic function but not repair functions; two small in-frame deletions; and one frameshift.